Oral epithelial cells of schoolchildren exposed to air pollution may develop cytotoxic and genotoxic damage: Daños citotóxicos y genotóxicos en células epiteliales orales de escolares expuestos a la contaminación atmosférica - García Zarate, Marco Antonio; Arellano García, María Evarista; González Acevedo, Zayre Ivonne; Torres Bugarín, Olivia (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2024)
As petrol stations emit pollutants into the atmosphere, their proximity to schools can affect air quality both inside and outside classrooms. School-age children, who spend five to seven hours a day in classrooms and playgrounds during the school year, may be at risk of inhaling potentially harmful gases and particles, which could have a negative impact on their health and academic performance. A biomonitoring study was carried out on 143 children from three schools. Two of the schools were considered to be exposed to volatile organic compounds (VOCs) and were located 50 and 300 metres away from petrol stations. The other school, which was not considered to be exposed, was located 450 metres away. With the exception of MN, the biomarkers of genotoxic damage were generally higher (p>0.05) in the school located 50 metres from a petrol station than in the control group, although the results were less clear in the school located 300 metres away. For all biomarkers (KR, CC, PN and KL), the school 50 metres from the source of emissions had higher levels of cytotoxicity (p <0.05). This is the first study to link exposure to volatile hydrocarbons in petrol to genotoxic damage in children, and it strongly suggests that urban planning laws should be changed to halt the decline in children's health.